1994
DOI: 10.1007/bf00174006
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of the tissue distribution and physiology of xanthine oxidoreductase

Abstract: Xanthine oxidoreductase is an enzyme which has the unusual property that it can exist in a dehydrogenase form which uses NAD+ and an oxidase form which uses oxygen as electron acceptor. Both forms have a high affinity for hypoxanthine and xanthine as substrates. In addition, conversion of one form to the other may occur under different conditions. The exact function of the enzyme is still unknown but it seems to play a role in purine catabolism, detoxification of xenobiotics and antioxidant capacity by produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 306 publications
0
29
0
4
Order By: Relevance
“…Therefore, in the reperfusion phase, high proportions of XO and its substrate hypoxanthine coincide with the other substrate, oxygen, thus producing ROS and tissue injury. This mechanism, accepted by many authors, has been studied mainly in warm experimental ischemia of the liver, and has shown contradictory results (7,8). In addition, injurious effects produced by circulating XO have also been reported, caused by production of ROS in organs other than those where the enzyme is released (9).…”
Section: Markers Was Higher In the Ce Of Patients With Moderate Primmentioning
confidence: 93%
“…Therefore, in the reperfusion phase, high proportions of XO and its substrate hypoxanthine coincide with the other substrate, oxygen, thus producing ROS and tissue injury. This mechanism, accepted by many authors, has been studied mainly in warm experimental ischemia of the liver, and has shown contradictory results (7,8). In addition, injurious effects produced by circulating XO have also been reported, caused by production of ROS in organs other than those where the enzyme is released (9).…”
Section: Markers Was Higher In the Ce Of Patients With Moderate Primmentioning
confidence: 93%
“…Consequently, XO uses molecular oxygen instead of NAD + during reperfusion and leads to formation of the free radical superoxide anion (O 2 .-) [15][16][17]. Superoxide anion can form hydrogen peroxide through superoxide dismutase activity and, in presence of iron, the extremely reactive hydroxyl radical by Fenton-type reactions [18,19].…”
mentioning
confidence: 99%
“…• -), which initiate reactions that produce a variety of free radical species including • OH and H 2 O 2 (Kooij 1994). These oxygen-derived radical species are hypothesized to oxidize DBAN and release CN -.…”
Section: Discussionmentioning
confidence: 98%